Effect of farmers’ field school (FFS) on maize production among women farmers in Ondo State (2019)
Farmer Field School (FFS) is a popular education and extension approach worldwide that uses experiential and group approaches to facilitate farmers in making decisions, solving problems, and learning new techniques. The study investigated the effect of FFS on women farmers’ production in Ondo State. Purposive sampling technique was used to select two local government areas based on the presence of women among the groups or women dominated groups. One hundred and sixty (160) respondents, comprising 80 participants and 80 nonparticipants were randomly selected. Data were collected with the use of interview schedule and analysed using frequencies, percentages, chi- square, Pearson product moment correlation and t-test αt 0.05 level of significance. The results indicated that more than half (51.9% ) had farm size of 0.5- 1.5 hectares, 49.4% affirmed high effect of FFS; 50.0% gained high knowledge, and 38% experienced between half and double increment on their level of production. There was significant relationship between marital status (χ2=7.73), level of education (χ2=14.09), motivating factors (r =0.673), knowledge gained (r=0.551) and the level of production of women farmers. There was significant difference in the level of production (t=13.450) between the participants of farmer field school and non- participants; and that participation in FFS impacted positively on the level of maize production of participants. Thus, it was recommended that government and non-government organizations should support FFS through adequate funding.